2017
DOI: 10.1177/0081246317698858
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of South African psychology interns’ perceptions of negative supervision events

Abstract: Prevalence rates of negative supervision events among Psychology interns in South Africa are non-existent. This article investigates the incidence of negative supervision events and explores the influence of various contextual variables on supervision outcomes. Quantitative data were obtained via a web survey from a sample (N = 92) of Clinical and Counselling psychology interns across nine provinces in South Africa. In all, 42 (or 45.6%) of the 92 participants had a negative supervision event during their inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Ellis et al () found that 36% of their sample ( N = 363) were currently receiving harmful supervision. Similar findings have been reported in other studies, where prevalence rates vary between 20% and 40% (Bang & Goodyear, ; Ellis, ; Ellis, Creaner, Hutman, & Timulak, ; Hendricks & Cartwright, ; Nelson & Friedlander, ; Ramos‐Sanchez et al, ). These prevalence rates are certainly a cause for concern and attention.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…Ellis et al () found that 36% of their sample ( N = 363) were currently receiving harmful supervision. Similar findings have been reported in other studies, where prevalence rates vary between 20% and 40% (Bang & Goodyear, ; Ellis, ; Ellis, Creaner, Hutman, & Timulak, ; Hendricks & Cartwright, ; Nelson & Friedlander, ; Ramos‐Sanchez et al, ). These prevalence rates are certainly a cause for concern and attention.…”
Section: Introductionsupporting
confidence: 89%
“…Contextual factors include factors like workload pressures (Hendricks & Cartwright, 2018), organisational culture (Davys & Beddoe, 2010) and challenges that emerge in the therapeutic process that are displaced onto the supervision relationship (Friedlander, 2015).…”
Section: Factors Associated With Harmful Supervisionmentioning
confidence: 99%
See 3 more Smart Citations